"At What Cost am I Doing This?" An interpretative phenomenological analysis of the experience of burnout among private practitioner psychotherapists. Issue 1 (28th October 2021) - Finan, Stephanie; McMahon, Aisling; Russell, Siobhán
Abstract: Burnout is an experience in response to chronic job stressors, understood to be composed of three components: exhaustion, cynicism and inefficacy. Burnout is an occupational hazard among psychotherapists that may result in poorer quality of care for clients and a diminished quality of life for clinicians. Several quantitative studies have shown that psychotherapists are at risk of developing burnout given the demanding nature of their work. While much research has been carried out with psychotherapists who work in organisations, there is a lack of available literature concerning the experience of the psychotherapy practitioner working in private practice. This study aimed to gain an understanding of psychotherapists' lived experiences of burnout while working exclusively in private practice in Ireland. Eight semi‐structured interviews were conducted and analysed using interpretative phenomenological analysis. Three superordinate themes were identified: (a) A Professional Identity Crisis: "maybe I just don't have what it takes?"; (b) The Embodiment of Burnout: "constantly running on red"; and (c) The Process of Rebalancing: "being real". The participants revealed a disillusionment with their career, alongside self‐criticism and shame for not meeting their internalised standards. They illuminated a profound felt sense of depletion and physical unwellness. They also shared their ongoing process of rebalancing rather than recovery from burnout. Participants universally described difficulty identifying and articulating burnout. The findings are discussed with reference to identity, embodiment of burnout and the process of rebalancing.